c+c*7+2=12

Simple and best practice solution for c+c*7+2=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for c+c*7+2=12 equation:


Simplifying
c + c * 7 + 2 = 12

Reorder the terms for easier multiplication:
c + 7c + 2 = 12

Reorder the terms:
2 + c + 7c = 12

Combine like terms: c + 7c = 8c
2 + 8c = 12

Solving
2 + 8c = 12

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 8c = 12 + -2

Combine like terms: 2 + -2 = 0
0 + 8c = 12 + -2
8c = 12 + -2

Combine like terms: 12 + -2 = 10
8c = 10

Divide each side by '8'.
c = 1.25

Simplifying
c = 1.25

See similar equations:

| 4(3n-7)+3=-3(-2n+8) | | 5b+9=7+2b | | -0.7w=5.6 | | 5x+27=2x+12 | | -11+9-2x-11-1=-13 | | 8t=400 | | (a+8)(a+2)=0 | | (x^2-x-1)(x^2-x-1)=5+x^3 | | (x^2-x-1)=5+x^3 | | (x^2-x-1)=5+x | | 7+4(3v-4)=-3(3v-3)+7v | | 4x-15=2x+9 | | x^7+2x^6-5x^5-13x^4-13x^3-5x^2+2x+1=0 | | 9w^2-75w-54= | | 5y-3=4(y+3) | | (8x+9)(2x+4)=0 | | 5n+3+9= | | 3d^2-13d+12= | | r+(-2)=-8 | | 3=8-x | | -3b+7=8b-3 | | x^2=52-9x | | 7u+3-2(-2u-3)=2(u-3) | | z^4=-16i | | -4x+2=-7x+11 | | 3x(5x+36)=180 | | -16s-126+4(4s+32)=0 | | 8.1=x-12.5 | | 4x-8=x-5+3x | | 4x+2(-2x+7)=16 | | 16t^2+35t+5=0 | | 37-15x=8 |

Equations solver categories